Analysis of Compensation Effect on Job Satisfaction under Foreign Capital Companies in the Manufacturing Sector - Chaidar, Diar Fachmi Rachmat (Journal of Business Management and Economic Development, 2024)
Because the level of employee satisfaction with the facilities provided by the company greatly influences the stability of the company, companies must be able to understand the needs of their employees. This study will investigate whether compensation also influences job satisfaction of foreign capital companies in the manufacturing industry in Karawang. This research uses the concept of descriptive and verification research, and the aim of descriptive research is to get an overview of the characteristics of the variable application of compensation and job satisfaction. The research results show that the compensation variables measured indicate that most middle line managers believe that employees receive compensation for all the work they do, whether in the form of money or not. So, research finds that compensation influences job satisfaction in a small way.